Efficiency of attenuating high-level acoustic impulses with double protection (earplugs and earmuffs used simultaneously) - J. Żera; R. Młyński (Archives of Acoustics)
The study aimed at attenuation obtained with simultaneously used earplugs and earmuffs (double protection) as opposed to hearing protective devices used singly. The measurements were conducted for high 170-dB peak SPL, 14-μs rise time, and 0.4-ms A duration acoustic impulses. Tests were conducted for light and heavy earmuffs, combined with foam and winged earplugs. The transmission loss method was used to assess the decrease in peak SPL and increase in A, C or D durations of waveforms of impulses recorded under the hearing protectors. The artificial test fixture (ATF, PN EN 24869-3) was used in the measurements modified to accommodate for conditions of double protection with a simultaneous use of an earmuff and an earplug. Results are discussed in relation to impulse noise damage risk criteria developed by CHABA, Pfander, and Smoorenburg. Double protection provides higher attenuation of peak SPL and a larger increase in the duration of impulses under hearing protectors, as compared to single protection of an earplug or an earmuff.